2010
DOI: 10.1161/circulationaha.109.875013
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein and Mortality in Patients Undergoing Coronary Angiography

Abstract: Background-The role of cholesteryl ester transfer protein (CETP) in the development of atherosclerosis is still open to debate. In the Investigation of Lipid Level Management to Understand its Impact in Atherosclerotic Events (ILLUMINATE) trial, inhibition of CETP in patients with high cardiovascular risk was associated with increased high-density lipoprotein levels but increased risk of cardiovascular morbidity and mortality. In this report, we present a prospective observational study of patients referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 22 publications
1
48
0
5
Order By: Relevance
“…201 Population studies that investigated CETP plasma concentrations as a biomarker also yielded results that contradict the initial genetic studies: Low rather than high CETP concentrations were associated with increased cardiovascular mortality in a nearly 8 years long follow-up of more than 3000 patients who underwent coronary angiography. 202 In the PROVE IT-TIMI 22 study, plasma CETP levels were not associated with differences in cardiovascular event rates. In the 50% of patients who reached the lowest concentrations of LDL-cholesterol by pravastatin treatment, a low CETP concentration was associated with excess cardiovascular event rates.…”
Section: Fibratesmentioning
confidence: 96%
“…201 Population studies that investigated CETP plasma concentrations as a biomarker also yielded results that contradict the initial genetic studies: Low rather than high CETP concentrations were associated with increased cardiovascular mortality in a nearly 8 years long follow-up of more than 3000 patients who underwent coronary angiography. 202 In the PROVE IT-TIMI 22 study, plasma CETP levels were not associated with differences in cardiovascular event rates. In the 50% of patients who reached the lowest concentrations of LDL-cholesterol by pravastatin treatment, a low CETP concentration was associated with excess cardiovascular event rates.…”
Section: Fibratesmentioning
confidence: 96%
“…In brief, incubation media contained 4 µl of donor liposomes and 10 µl of total plasma, as a source of CETP and endogenous lipoprotein substrates, in a fi nal volume of 200 µl TBS. Incubations were performed in triplicate for 1 h at 37°C in a FL600 Microplate Fluorescence Reader (Bio-Tek, Winooski, not all ( 7,8 ) human studies consequently reported a positive association between plasma CETP activity and atherosclerotic cardiovascular disease (CVD) morbidity and mortality. Especially in the setting of the metabolic syndrome, including type 2 diabetes mellitus and hypertriglyceridemia, the predictive value of increased CETP mass and activity for CVD events is particularly strong ( 9 ).…”
Section: Measurement Of Cetp Activitymentioning
confidence: 99%
“…In 3 of these studies there was a significant inverse relationship between ASCVD and CETP concentration, [35][36][37] whereas in another there was no statistically significant association. 32 The fifth study identified a significant positive relationship between the concentration of CETP and ASCVD in people with elevated levels of plasma triglyceride but not in those with low triglyceride levels.…”
Section: Human Population Studies In Which the Concentration Of Cetp mentioning
confidence: 95%